(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
Performance Automation is a technique which helps in determining the performance of the system, by determining various system parameters under different workloads. This project aims at developing the framework for determining the performance. It mainly captures system level CPU and memory consumption during any of the operations being performed. Whenever any operation is done in CMRepo, the communication takes place between client and CMRepo server. This server hence communicates with relay, and relay to proxy. Therefore, this framework also helps in capturing the timestamps for each of the messages that are communicated between client, server, relay and proxy. CPU and Memory consumption, along with total time taken to complete the whole operation help in determining the performance of CMRepo. This project is done using Python scripting and Unix commands. This paper describes the designed framework that helps in determining the overall performance of CMRepo. If the determined performance is not matching with the threshold values, it means that the operation is not successful or if there’s any issue or bug within the product. The data is captured at the idle condition of the system as well as when the operation is performed. This helps in giving clear picture of how the system is performing at various conditions.